2007
DOI: 10.1111/j.1524-4733.2007.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Related to Oral versus Subcutaneous Iron Chelation: A Time Trade-off Study

Abstract: Community respondents associate oral administration of an iron chelator such as deferasirox with enhanced QoL compared with subcutaneous treatment. Assuming equal safety and efficacy, QoL gains from once-daily oral treatment compared with subcutaneous infusion are significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 12 publications
6
39
1
1
Order By: Relevance
“…Aspects of convenience valued can be classified broadly into two categories: Those relating to the administration of an intervention, for example, dosing frequency or mode of administration [13,15,18,19,21,23,24,26,[30][31][32][33][34][36][37][38][39], and those looking at ease of access to an intervention, for example, distance to travel [14,16,17,20,25,28,29,35]. Two studies spanned both categories [22,27].…”
Section: Key Characteristics Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Aspects of convenience valued can be classified broadly into two categories: Those relating to the administration of an intervention, for example, dosing frequency or mode of administration [13,15,18,19,21,23,24,26,[30][31][32][33][34][36][37][38][39], and those looking at ease of access to an intervention, for example, distance to travel [14,16,17,20,25,28,29,35]. Two studies spanned both categories [22,27].…”
Section: Key Characteristics Of Studiesmentioning
confidence: 99%
“…Studies identified and reviewed were published between 1996 and 2013, and came from Canada (n ¼ 7) [13][14][15][16][17][18][19], the United States (n ¼ 3) [20][21][22], the United Kingdom (n ¼ 3) [23][24][25], Scotland (n ¼ 3) [26][27][28], Australia (n ¼ 3) [29][30][31], Sweden (n ¼ 2) [32,33], Denmark (n ¼ 1) [34], Germany (n ¼ 1) [35], Italy (n ¼ 1) [36], and Spain (n ¼ 1) [37]. Two studies had multinational perspectives [38,39].…”
Section: Key Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6] The once-daily oral deferasirox dispersible tablet (DT) formulation (Exjade ® ), available since 2005, offered an improved option over parenteral deferoxamine (Desferal ® ), providing greater compliance, patient satisfaction, and health-related quality of life. 7,8 The efficacy and safety of deferasirox DT has been well-defined through an extensive clinical trial program in adult and pediatric patients with a variety of anemias, including thalassemia, myelodysplastic syndromes (MDS), sickle-cell disease, and other rare anemias, [9][10][11][12][13] and has been used in clinical practice worldwide for over a decade. Nonetheless, barriers to optimal patient acceptance of treatment still exist with deferasirox DT, including palatability, the need to take the drug in a fasting state (ie, not being able to take with food), and drug-related side effects, notably gastrointestinal (GI) tolerability.…”
Section: Introductionmentioning
confidence: 99%
“…As the disease progresses and relapses occur, patients may increasingly experience symptoms such as fatigue and depression [1,2]. A reduction in QOL may occur as a result of one or more treatment-related factors, including dissatisfaction with administration route, the need for frequent administration of therapy, the development of side effects or a perceived lack of treatment efficacy [3][4][5][6]. In addition, the relative importance assigned to different treatment outcomes may vary among patients.…”
Section: Introductionmentioning
confidence: 99%